Classical genetic research and its legacy : the mapping cultures of twentieth-century genetics - Rheinberger, Hans-Jörg; Gaudillière, Jean-Paul, 1957- (Routledge studies in the history of science, technology, and medicine, 2004)
With the rise of genomics, the life sciences have entered a new era. This book provides a comprehensive history of mapping procedures as they were developed in classical genetics.